Efektivitas Kombinasi Media Audiovisual Aku Bangga Aku Tahu Dan Diskusi Kelompok Dalam Upaya Meningkatkan Pengetahuan Remaja Tentang HIV-AIDS - Ifroh, Riza Hayati; Ayubi, Dian (UI Scholars Hub, 2018)
Background. The Indonesian government has a target of 95% adolescents have knowledge about HIV-AIDS throughout Indonesia. East Kalimantan as one of the provinces in Indonesia showed that the level of adolescents knowledge Samarinda reached 25.5% in 2012. Aim. Study aim is to assess effectiveness of Aku Bangga Aku Tahu audiovisual Mmedia and group discussion to improve teenager’s knowledge on HIV-AIDS. Method. The study design used was quasi experimental on the primary data consisted of 80 research subjects in SMAN 1 and SMAN 3 Samarinda. Data analysis are univariate and bivariate analysis by using the Wilcoxon and Mann Whitney. Result . The results showed that after the intervention to intervention and control groups experienced an increase in knowledge about HIV-AIDS. The increased of adolescents knowledge about HIV-AIDS in the intervention group amounted to 22,41% and increased of knowledge about HIV - AIDS adolescents in the control group was 21,6%. In addition, there is no statistically significant difference in the change in the value of knowledge of HIV-AIDS among the intervention group (film screening and discussion group) and control group (film screening).